Deciding the Best Location for RM Bunut Sari to Open A New Branch in Greater Bandung - Ichsan Ramadhan Prawira; Utomo Sarjono Putro (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research aims to support the Sundanese restaurant RM Bunut Sari in determining the optimal location for opening a new branch in the Greater Bandung area of West Java. Environmental analysis is conducted by assessing the internal capabilities of RM Bunut Sari and examining external market conditions in Bandung City, Bandung Regency, and West Bandung Regency. Analytical Hierarchy Process (AHP) modeling is then utilized to evaluate which alternative location offers the greatest strategic advantages. Based on comparisons across decision criteria such as parking facilities, building size, visibility, distance from competitors, and property prices, Bandung Regency emerges as the recommended location. An implementation plan details the necessary launch activities spanning site selection, renovation, licensing and permissions, staffing, promotions, and eventual restaurant opening. The recommendations highlight leveraging RM Bunut Sari’s existing strengths in taste quality and service experience while closely monitoring operational and marketing outcomes from the new branch. Thus the analytical approach delivers an optimized location choice for RM Bunut Sari’s expansion, guided by environmental analysis and multi-criteria decision making.